Effects of nutrients on cone losses of stone pine (Pinus pinea L.) in Kozak Basin - Kilci M. (Mediterranean stone pine for agroforestry, 2013)
Kozak Basin is located in Bergama District in Izmir Province. The basin is a bowl-shaped stone pine forest area, with a size of 16,000 hectares, which occupies one-third of the total stone pine area in Turkey. Almost all the forest area in the Basin is private. In recent years, cone losses of stone pine have increased. For this reason, in this study 8 different areas were examined to determine the relations between cone losses and nutrients over the 2005-2008 period. Almost all of cone losses occurred in the new conelets according to the results of cone counting in the sampling area. Therefore, evaluations were conducted based on this period. Significant differences in cone losses were found between years and localities. To determine the relationship between cone losses and nutrients, one-, two- and three-year old needles were taken from the sample trees and their size and weight were measured, then the samples were analysed in terms of micro- and macro nutrients. Soil samples were taken beneath the same sample trees and analysed. By examining the relationship between cone losses and nutrients in the needles, a negative correlation between cone losses and nitrogen (N), phosphorus (P), calcium (Ca) and manganese (Mn) could be determined. In other words, when these nutrients diminished, cone losses increased. It is considered that among these elements, especially P and Ca combined with drought could be a factor in cone losses.
AGROPINE 2011 International Meeting on Mediterranean Stone Pine for Agroforestery, 2011/11/17-19, Valladolid (Spain)